Leaders’ Gender, Perceived Abusive Supervision and Health - Stempel, Christiane R.; Rigotti, Thomas (Frontiers in Psychology, 2018)
Purpose: We investigated the role of gender in abusive leadership practices, along with the effects of abusive leadership on employee health. We tested two hypotheses regarding the relationship between abusive leadership practices and subordinates’ health outcomes. Design: At two points of measurement, 663 participants in Germany rated their 158 direct team leaders on abusive supervision and stated their own levels of emotional exhaustion and somatic stress. To test our hypotheses, we used a mixed model approach. Findings: The results show no gender differences between the ratings for female and male leaders regarding abusive supervision but do confirm that the leaders’ gender did play a role in employees’ perceptions of abuse; perceived abusive supervision is more strongly related to increased emotional exhaustion and somatic stress when the leader is male. Limitations: The generalizability of the study is limited due to a majority of females in the sample. Practical Implications: Organizations should review their policies and procedures to first identify abusive supervision, then to offer adequate support programs for both leaders and subordinates. Originality/Value: The study integrates gender into research on leadership and health, shifting the focus from previous studies that investigated constructive to destructive leadership. A further strength of the study is the application of a multilevel design and two separate points of measurement.